Induction of antinuclear antibodies in patients with rheumatoid arthritis receiving treatment with human recombinant interferon gamma. Issue 8 (August 1988) - Seitz, M; Franke, M; Kirchner, H
Abstract : Of six patients with rheumatoid arthritis (RA) treated with human recombinant interferon gamma for two to eight months, three developed antinuclear antibodies (ANAs). This was accompanied by a simultaneous clinical exacerbation of the disease activity. In this study both anti-inflammatory and immunostimulatory effects of human recombinant interferon gamma in patients with RA were observed.